1997
DOI: 10.1530/eje.0.1360608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural menopause on serum levels of IGF-I and IGF-binding proteins: relationship with bone mineral density and lipid metabolism in perimenopausal women

Abstract: The present study was performed to examine the effect of natural menopause on serum levels of IGF-I, IGF-binding protein (IGFBP)-2 and -3 as well as on bone mass and lipid metabolism in perimenopausal women. One hundred and twenty-one healthy Japanese women, who were 45-55 years old, were studied (71 premenopausal and 50 postmenopausal women 1-9 years after menopause). Bone mineral density (BMD) was measured at the middle third of the radius by using dual energy X-ray absorptiometry. Serum levels of IGF-I, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Blood levels of growth hormone, IGF-I and prolactin also decline with increasing age (Hall et al, 1999). Prolactin levels are also permanently reduced by pregnancy, and are lower after the menopause than before (Reyes et al, 1977;Wang et al, 1988;Metka et al, 1995;Nasu et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Blood levels of growth hormone, IGF-I and prolactin also decline with increasing age (Hall et al, 1999). Prolactin levels are also permanently reduced by pregnancy, and are lower after the menopause than before (Reyes et al, 1977;Wang et al, 1988;Metka et al, 1995;Nasu et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our clinical studies showed that the suppression of the GH-insulin-like growth factor-I (IGF-I) axis was partly associated with age-dependent bone loss as well as bone loss after gonadal failure [5,6]. The adult skeleton is cycli cally remodelled by osteoclastic bone resorption followed by osteoblastic bone formation -the cavities excavated by osteoclasts are subsequently refilled by osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study revealed that an age-related decline in GH secretion was involved in age-dependent bone loss and changes in body composition in elderly women (14). The present study focusing on perimenopausal women indicates that GH itself plays a crucial role in the physiological regulation and maintenance of bone mass and body composition.…”
Section: Biochemical Measurementsmentioning
confidence: 49%